2015
DOI: 10.5966/sctm.2015-0074
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12Gene Therapy Ameliorates Ischemia-Induced White Matter Injury in Mouse Brain

Abstract: Remyelination is an important repair process after ischemic stroke-induced white matter injury. It often fails because of the insufficient recruitment of oligodendrocyte progenitor cells (OPCs) to the demyelinated site or the inefficient differentiation of OPCs to oligodendrocytes. We investigated whether CXCL12 gene therapy promoted remyelination after middle cerebral artery occlusion in adult mice. The results showed that CXCL12 gene therapy at 1 week after ischemia could protect myelin sheath integrity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 39 publications
(53 reference statements)
1
41
0
Order By: Relevance
“…By overexpression of Netrin-1 or CXCL12 gene in OPCs, studies showed those factors promote OPCs proliferation, migration, axon remyelination, further facilitating white matter repair and remodeling, which provides a therapeutic perspective for targeting NG2-glia in ischemia. 62,63 These conclusions, however, need to be further confirmed in vivo. A recent study reported that NG2-glia can be reprogramed into both glutamatergic and GABAergic neurons after NeuroD1 expression in the brain, opening a completely new direction in the therapy of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…By overexpression of Netrin-1 or CXCL12 gene in OPCs, studies showed those factors promote OPCs proliferation, migration, axon remyelination, further facilitating white matter repair and remodeling, which provides a therapeutic perspective for targeting NG2-glia in ischemia. 62,63 These conclusions, however, need to be further confirmed in vivo. A recent study reported that NG2-glia can be reprogramed into both glutamatergic and GABAergic neurons after NeuroD1 expression in the brain, opening a completely new direction in the therapy of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 94%
“…These alterations have direct and/or indirect effects on neurons and other glial cell populations during and after ischemia. By overexpression of Netrin‐1 or CXCL12 gene in OPCs, studies showed those factors promote OPCs proliferation, migration, axon remyelination, further facilitating white matter repair and remodeling, which provides a therapeutic perspective for targeting NG2‐glia in ischemia . These conclusions, however, need to be further confirmed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted genes were delivered to the ischemic area, which promoted focal angiogenesis, neurogenesis, and finally improved ischemic tissue metabolism and functional recovery. [2][3][4] Matrix metalloproteinase-9 (MMP-9) has been found to play dual roles after ischemia, with its detrimental upregulation in the acute phase but beneficial elevation in the delayed phase. 5,6 Because excessive MMP-9 expression could lead to brain edema and hemorrhagic transformation, approaches to modulate the MMP-9 expression level in the delayed phase of stroke may be attractive.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, survival-supporting effects mediated via the second CXCL12 receptor, CXCR7, have been reported for neural progenitor cells [19]. Recently, a specific contribution of SDF-1 to the differentiation of oligodendrocyte precursor cells (OPCs), the myelin producing cells in the CNS, and remyelination after traumatic and inflammatory insults, via the chemokine receptors CXCR4 and CXCR7, have been demonstrated in vivo and in vitro [7,12,15,20,21]. This evidence supports the hypothesis that chemokine receptors participate in the inflammatory reactions during CNS diseases via specific mechanisms in addition to evoking leukocyte responses.…”
Section: Introductionmentioning
confidence: 99%